Evaluasi Program Pemerintah Kota Tomohon Terhadap Pengurangan Sampah Plastik Di Kelurahan Kampung Jawa - Wanget, Samuel Wailan Leonard; Taasiringang, Gloria; Daluwu, Frisca Jellyani; Agama, Harlinda; Gumansalangi, Prisca; Sasehang, Juandry; Wasida, Marchella; Auif, Rut Serina; Mandalika, Tesalonika; Sumenda, David Chara; Tarelluan, Samantha; Taarae, Kesya; Mamarodia, Laidy Tirsa; Tamusa, Myrina Monika; Poli, Paulina Gledis; Larengkeng, Veronika; Wattimena, Priskila Julia (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Tomohon, renowned for its spotless and beautiful environment, is often referred to as the "City of Flowers." Consequently, the Tomohon City Government has implemented a program focused on environmental cleanliness. However, the effective implementation of this program in Kampung Jawa Village has faced challenges. This qualitative, observative participatory study evaluated the program's execution in Kampung Jawa through direct observation. The findings indicate that the municipal program has not been fully realized due to a lack of public awareness regarding cleanliness and waste management. Despite these shortcomings, the program has the potential to reduce plastic waste in Kampung Jawa significantly. A thorough evaluation of plastic waste usage in the area could optimize the community's environment towards a zero-waste goal.